2016
DOI: 10.14400/jdc.2016.14.12.345
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Reflection, Critical Thinking Disposition, Muti Cultural Experience and Cultural Competence in nursing students

Abstract: As Korea has been rapidly transformed to be a multi cultural society, it becomes essential for nursing provider to develop cultural competency. The purpose of this study was to identify impact of self-reflection, critical thinking disposition and multi cultural experience on nursing student's cultural competence. A convenience sample of 148 nursing students was obtained from a university in Gyeonggi Province. Data was analyzed using Pearson correlation and multiple regression. Significant relationships were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Lee and Lee 1) also found that empathic ability was correlated with cultural knowledge and skill. Along with the results of other studies, this study confirmed that critical thinking and empathic ability were basic elements of cultural competency 1,12,15,16) .…”
Section: Discussionsupporting
confidence: 88%
“…Lee and Lee 1) also found that empathic ability was correlated with cultural knowledge and skill. Along with the results of other studies, this study confirmed that critical thinking and empathic ability were basic elements of cultural competency 1,12,15,16) .…”
Section: Discussionsupporting
confidence: 88%